Efficacy of virtual reality exercise in knee osteoarthritis rehabilitation: a systematic review and meta-analysis - Wei, Wei; Tang, Haiting; Luo, Yu; Yan, Shichang; Ji, Qipei; Liu, Zhixiang; Li, Huaqiang; Wu, Fei; Yang, Shenqiao; Yang, Xin (Frontiers in Physiology, 2024)
Background: This systematic review and meta-analysis aims to investigate the effects of virtual reality (VR) exercise compared to traditional rehabilitation on pain, function, and muscle strength in patients with knee osteoarthritis (KOA). Additionally, the study explores the mechanisms by which VR exercise contributes to the rehabilitation of KOA patients. Methods: We systematically searched PubMed, the Cochrane Library, Embase, Web of Science, Scopus, and PEDro according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Our search spanned from the library construction to May 24, 2024, focusing on randomized controlled trials (RCTs). Primary outcomes included pain, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and muscle strength. Meta-analysis was conducted using RevMan (version 5.4) and Stata (version 14.0). The bias risk of included studies was assessed using the Cochrane RoB 2.0 tool, while the quality of evidence was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Results: This meta-analysis and systematic review included 9 studies involving 456 KOA patients. The results indicated that VR exercise significantly improved pain scores (SMD, –1.53; 95% CI: –2.50 to –0.55; p=0.002), WOMAC total score (MD, –14.79; 95% CI: –28.26 to –1.33; p=0.03), WOMAC pain score (MD, –0.93; 95% CI: –1.52 to –0.34; p=0.002), knee extensor strength (SMD, 0.51; 95% CI: 0.14 to 0.87; p=0.006), and knee flexor strength (SMD, 0.65; 95% CI: 0.28 to 1.01; p=0.0005), but not significantly for WOMAC stiffness (MD, –0.01; 95% CI: –1.21 to 1.19; p=0.99) and physical function (MD, –0.35; 95% CI: –0.79 to –0.09; p=0.12). Conclusions: VR exercise significantly alleviates pain, enhances muscle strength and WOMAC total score in KOA patients, but improvements in joint stiffness and physical function are not significant. However, the current number of studies is limited, necessitating further research to expand on the present findings.